Budaya Jawa “Reog Ponorogo” sebagai Bahan Ajar Bahasa Indonesia bagi Penutur Asing dalam Mendukung Internasionalisasi Bahasa Indonesia - Audrey Zhafira Salma; Gita Hapsari; Laksmita Dwi Alea Casta; Retno Kurnianingsih; Kundharu Saddhono (Asosiasi Riset Ilmu Pendidikan Indonesia, 2025)
Indonesian as a national language seeks to be internationalized through the teaching of BIPA, which requires subject matter that includes linguistic and cultural elements. Teaching often focuses on vocabulary and grammar, neglecting the important cultural context. Javanese culture, particularly the performing art of Reog Ponorogo, can be used as an effective medium of communication and teaching. Through this approach, BIPA teaching can be integrated with immersive cultural experiences, enhancing the understanding of Indonesian language and culture among foreign speakers. In this study, we aim to develop BIPA teaching materials by using local culture such as Reog Ponorogo. In qualitative research, the results emphasize meaning rather than generalization, data collection methods are triangulated, and data analysis is done inductively. The data used were sourced from various books, scientific journals, and the results of a survey of the needs of BIPA teaching materials for foreign speakers at Yale University. The integration of culture in teaching materials, such as the traditional art of Reog Ponorogo, not only enriches the learning experience, but also helps learners understand the social context and values underlying language use. Reog Ponorogo, with its deep symbolism and philosophy, provides an opportunity for learners to not only acquire language proficiency, but also develop Indonesian cultural values and character.